Atitude de criadores de bovinos de corte com relação à vacina antiaftosa em dois municípios de Minas gerai s - Machado Filho , Francisco; Ferreira de Toledo , Eros; Ernandes Ribeiro da Cruz , Flávio; Guerrero , Solon J (Revista Ceres, 2025)
The present study examined the attitudes of cattle farmers with regard to the vaccination program. A random sample of 96 farmers in two municípios (counties) were surveyed using a series of individual, technological and structural aspects as independent variables. Data were analyzed using a series of scales to measure the variables.